High-risk & critical care obstetrics - Troiano, Nan H.; Harvey, Carol J.; Chez, Bonnie Flood. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"The edition includes extensive revisions that reflect evidence-based changes in clinical practice for specific complications, and new chapters have been added that address foundations for practice, adjuncts for clinical practice, and selected clinical guidelines"--Provided by publisher.